The Term Asset-Backed Securities Loan Facility - Elizabeth Caviness; Asani Sarkar; Ankur Goyal; Woojung Park (Federal Reserve Bank of New York, 2021)
The COVID-19 pandemic disrupted the asset-backed securities (ABS) market, resulting in higher spreads on ABS and briefly halting the issuance of some ABS. On March 23, 2020, the Federal Reserve established the Term Asset-Backed Securities Loan Facility (TALF) to support the flow of credit to consumers and businesses by re-enabling the issuance of ABS. In this paper, we describe how TALF works, how much it was used, and its effect on the issuance and spreads of TALF-eligible securities relative to those of TALF-ineligible securities. We find that both the introduction of TALF and its subsequent expansion were associated with statistically significant declines in the spreads of TALF-eligible relative to TALF-ineligible ABS. However, the facility did not have a statistically significant effect on issuance. Finally, we compare TALF with an earlier version of the facility that was implemented during the global financial crisis and discuss lessons learned from implementing the program.
Keywords: G01; G18; G23; 330; TALF; COVID crisis; Fed facility; securitization; ABS market; Federal Reserve lending facilities